The dual role of cannabidiol on monocyte-derived dendritic cell differentiation and maturation - Pénzes, Zsófia; Alimohammadi, Shahrzad; Horváth, Dorottya; Oláh, Attila; Tóth, Balázs István; Bácsi, Attila; Szöllősi, Attila Gábor (Frontiers in Immunology, 2023)
Extracts and compounds isolated from hemp (Cannabis sativa) are increasingly gaining popularity in the treatment of a number of diseases, with topical formulations for dermatological conditions leading the way. Phytocannabinoids such as (-)-cannabidiol, (-)-cannabinol and (-)-Δ 9 -tetrahydrocannabivarin (CBD, CBN, and THCV, respectively), are present in variable amounts in the plant, and have been shown to have mostly anti-inflammatory effects both in vitro and in vivo, albeit dominantly in murine models. The role of phytocannabinoids in regulating responses of dendritic cells (DCs) remains unclear. Our research therefore aimed to investigate the effects of CBD, CBN, and THCV on human DCs differentiated from monocytes (moDCs). Phytocannabinoids did not influence the viability of moDCs up to 10 μM, and only CBD had effects on maturational markers of moDCs, and neither compound influenced LPS-induced activation at 10 μM. Since only CBD had measurable effects on moDCs, in our subsequent experiments we tested the effect only of that pCB. On moDCs differentiated in the presence of CBD subsequent activation by LPS induced a markedly different, much more tolerogenic response. CBD-treated moDCs also produced significantly more interleukin (IL)-6, TNFα and, importantly, IL-10 in response to LPS, which shows a shift toward anti-inflammatory signaling, as well as a more robust secretory response in general. To rule out the possibility that these effects of CBD are specific to TLR4 signaling, we determined the effect of CBD on TLR7/8-induced maturation as well, and saw similar, although less marked responses. CBD-treated moDCs were also less efficient at activating naïve T cells after LPS stimulation, further supporting the tolerogenic effect of this phytocannabinoid on moDCs. Reactome pathway analysis showed an inflammatory response to LPS in moDCs, and to a lesser extent to CBD as well. In contrast CBD-treated moDCs responded to LPS with a shift towards a more tolerogenic phenotype, as IL-10 signaling was the most prominently induced pathway in this group. Our results show that CBD achieves an anti-inflammatory effect on adaptive immune responses only in the presence of an activating stimuli on moDCs by reprogramming cells during long-term treatment, and not through acute, short-term effects.